Estrategias de estimulación visual para el desarrollo del lenguaje en niños de primer grado, escuela de EGB Dr. Reinaldo Espinosa Aguilar 2023-2024 - Acaro Cañar, Jessica Alexandra (2024)
This research was oriented to improve language development through visual strategies such as: reading stories with images, vocabulary cards, image puzzles, among others, which allows an adequate education in infants. From this perspective, the general objective is to determine the incidence of visual stimulation strategies in the development of language in first grade children. And as specific objectives, to diagnose the strategies that can be used to develop language in children, to select visual stimulation strategies to improve language in children, and to present a guide of didactic-pedagogical activities of visual stimulation to promote language. The research is descriptive, since the information was presented as it occurred in its natural context; it consists of a non-experimental design, since the variables were not modified. It also has a qualitative approach, since it was possible to understand and approach the object of study; the methods used were hermeneutic, analytical, synthetic, inductive and deductive. Among the techniques used were observation and interview with their respective instruments, followed by the participation of 1 teacher and 31 students selected by a type of non-probabilistic sampling (by convenience) obtaining a total of 32 participants. In relation to the results, it has been significantly determined the importance of visual stimulation for language development, through the implementation and development of activities that include visual materials that not only improve the linguistic skills of students, but also increase their ability to express emotions, interests, opinions and needs.